The Role of Vitamin D in Enchancing Immune System and Preventing Stunting in Pediatric Patients: Literature Review - Mohamad Soleh; Khafifah Puja Atmalia; Citra Kharisma Zulfa; Muhammad Irfan; Kevin Tandarto (Indonesian Journal of Global Health Research, 2025)
The problem of stunting in Indonesia is a problem that has become a national concern. Stunting is caused by a lack of macro and micro nutrients. Vitamin D is one of the micronutrients that is important for growth in pediatric patients.Objectives of the studyo determine and examine the relationship between vitamin D and the immune system and prevention of stunting in pediatric patientsMethods: Literature searches were obtained through reference sources from Google Scholar, PubMed, Proquest, EBSCOhost. Inclusion criteria for the literature review were original articles, published in Indonesian and English, and receiving vitamin D therapy. A review of the literature highlights the crucial role of vitamin D in bone metabolism, growth, and immune system regulation, particularly in children. These functions contribute to the prevention of stunting. During pregnancy, vitamin D is essential for immune modulation in the fetus-mother interaction, making it a key regulatory factor. Its non-classical roles include acting as a strong immunomodulator by enhancing antibacterial defenses and regulating T-lymphocytes to reduce inflammation and promote immune tolerance. In the decidua, vitamin D supports innate immunity by enhancing infection response while preventing excessive immune-related inflammation. Current research has explored its potential in reducing the risk of infectious diseases like tuberculosis and in modulating autoimmune conditions. Vitamin D influences immune function beyond its direct role in the primary innate response. Early prevention of stunting requires sufficient intake of both macronutrients and micronutrients. Micronutrients, particularly vitamin D, play a vital role in bone metabolism and contribute to strengthening the body's defense mechanisms, helping to reduce the risk of infectious diseases in children.